Fabrication of ZIF‐8@Polyphosphazene core‐shell structure and its efficient synergism with ammonium polyphosphate in flame‐retarding epoxy resin. (23rd January 2020) - Lv, Xinyao; Zeng, Wei; Yang, Zhiwang; Yang, Yaoxia; Wang, Yun; Lei, Ziqiang; Liu, Jinling; Chen, Denglong
Abstract : A novel zeolitic imidazolate framework (ZIF‐8) nanoparticles@polyphosphazene (PZN) core‐shell architecture was synthesized, and then, ZIF‐8@PZN and ammonium polyphosphate (APP) were applied for increasing the flame retardancy and mechanical property of epoxy resin (EP) through a cooperative effect. Herein, ZIF‐8 was used as the core; the shell of PZN was coated to ZIF‐8 nanoparticles via a polycondensation method. The well‐designed ZIF‐8@PZN displayed superior fire retardancy and smoke suppression effect. The synthesized ZIF‐8@PZN observably raised the flame retardancy of EP composites, which could be demonstrated by thermogravimetric analysis (TGA) and a cone calorimeter test (CCT). The chemical structure of ZIF‐8@PZN was characterized by X‐ray diffraction (XRD), X‐ray photoelectron spectroscopy (XPS), and transmission electron microscopy (TEM). Compared with pure epoxy, with the incorporation of 3 wt% ZIF‐8@PZN and 18 wt% APP into the EP, along with 80.8%, 72.6%, and 64.7% decreased in the peak heat release rate (pHRR), the peak smoke production rate (pSPR), and the peak CO production rate (pCOPR), respectively. These suggested that ZIF‐8@PZN and APP generated an intumescent char layer, and ZIF‐8@PZN can strengthen the char layer, resulting in the enhancement in the flame resistance of EP.